Charmed-meson scattering on nucleons in a QCD Coulomb gauge quark model - Antunes, S. M. [UNESP]; Krein, G. [UNESP]; Vizcarra, V. E. [UNESP] (FapUNIFESP (SciELO), 2007)
The scattering of charmed mesons on nucleons is investigated within a chiral quark model inspired on the QCD Hamiltonian in Coulomb gauge. The microscopic model incorporates a longitudinal Coulomb confining interaction derived from a self-consistent quasi-particle approximation to the QCD vacuum, and a traverse hyperfine interaction motivated from lattice simulations of QCD in Coulomb gauge. From the microscopic interactions at the quark level, effective meson-baryon interactions are derived using a mapping formalism that leads to quark-Born diagrams. As an application, the total cross-section of heavy-light D-mesons scattering on nucleons is estimated.
Keywords: Charmed mesons; Coulomb gauge; Hadron-hadron interactions; Quantum chromodynamics; Quark model